Analisis Kerangka Kerja IT Governance Untuk Memitigasi Risiko Serangan Siber Pada Perusahaan Di Sektor Jasa Keuangan - Rachman, Riyandi Patu; Firmansyah, Gerry; Akbar, Habibullah; Widodo , Agung Mulyo (Riviera Publishing, 2025)
Cybersecurity has become a critical issue for the financial services sector, which increasingly relies on information technology. Limited resources and inadequate Governance make this sector vulnerable to cyberattacks, which can lead to financial losses, data breaches, and operational disruptions. Therefore, implementing an effective IT Governance Framework is essential to enhance cyber resilience and mitigate attack risks. This study aims to analyze the role of IT Governance in mitigating cyberattack risks for companies in the financial services sector. The research employs a qualitative approach through case studies, interviews, and analysis of relevant documents. The findings indicate that most financial service companies still have low preparedness levels in facing cyber threats. Proper implementation of IT Governance can help improve protection and response to attacks, despite challenges in resources and security awareness.